Tìm X \(\dfrac{x-1}{2017}+\dfrac{x-2}{2016}=\dfrac{x-3}{2015}+\dfrac{x-4}{2014}\)
tìm x biết (\(\dfrac{1}{2}\)+\(\dfrac{1}{3}\)+\(\dfrac{1}{4}\)+...+\(\dfrac{1}{2018}\)).x=\(\dfrac{2017}{1}+\dfrac{2016}{2}+\dfrac{2015}{3}+...+\dfrac{2}{2016}+\dfrac{1}{2017}\)
Tìm x biết \(\dfrac{x+4}{2015}+\dfrac{x+3}{2016}=\dfrac{x+2}{2017}+\dfrac{x+1}{2018}\)
Tìm x , biết ;
\(\dfrac{x+1}{2016}+\dfrac{x+2}{2015}=\dfrac{x+3}{2014}+\dfrac{x+4}{2013}\)
\(\dfrac{x+4}{2000}+\dfrac{x+3}{2001}=\dfrac{x+2}{2002}+\dfrac{x+1}{2003}\)
Tìm x nguyên biết:
a)\(\dfrac{1}{1.3}+\dfrac{1}{3.5}+\dfrac{1}{5.7}+...+\dfrac{1}{\left(2x-1\right).\left(2x+1\right)}=\dfrac{49}{99}\)
b)\(1-3+3^2-3^3+...+\left(-3\right)^x=\dfrac{9^{1006}-1}{2}\)
tìm x
\(\dfrac{x+4}{2000}+\dfrac{x+3}{2001}=\dfrac{x+2}{2002}+\dfrac{x+1}{2003}\)
Giá trị \(x\) thoả mãn \(\dfrac{x}{2}+\dfrac{x}{4}+\dfrac{x}{2016}=\dfrac{x}{3}+\dfrac{x}{5}+\dfrac{x}{2017}\) là \(x\)=
Tìm x biết \(\dfrac{1}{3}+\dfrac{1}{6}+\dfrac{1}{10}+......+\dfrac{2}{x.\left(x+1\right)}=\dfrac{2016}{2018}\)